Analysis of the Efficiency of Brown Rice Commerce in Batang Anai District, Padang Pariaman Regency, West Sumatra Province - Yusri Usman; M. Refdinal; Rusja Rustam (Journal of Social Research, 2023)
In the sale of produce, it is often found that farmers get a low proportion of profits and intermediary traders get a high proportion of profits. This study aims to analyze the profit efficiency of its commercial institutions. This study used a survey method by sampling brown rice farmers as many as 7 farmers by census and a sample of intermediary traders based on the involvement of commerce with farmers. This study used a proportional analysis of the profits of commercial institutions that participated in the brown rice business. From the results of the study, 2 kinds of brown rice business channels were obtained, namely 1). Consumer Merchant/Reseller Farmer, 2) Farmer Collecting merchant/Consumer Reseller. From the analysis, it is obtained that on business channel 1 the profit received is equal to the proportional profit because it is a direct business channel. In the tataniaga channel 2, the profits of the commercial institutions are disproportionate where the farmer gets the profit received lower than the proportional profit and the collector/retailer gets the profit received higher than the proportional profit, so the tataniaga channel 2 is inefficient. It is recommended to hold agricultural business analysis counseling to farmers about calculating the cost of farming, awareness to farmers that selling products is a business problem, and provide market information to farmers.ààà